Il discorso sui diritti umani dei migranti e dei rifugiati nei programmi elettorali delle elezioni europee del 2024 in Spagna e Italia. Una riflessione dopo il 75° anniversario della Dichiarazione Universale dei Diritti Umani - Jorge Alonso, Ana; Gianturco, Giovanna; Nocenzi, Mariella (Studi Politici, 2025)
The elections for the renewal of the European Parliament in June 2024 offered a representation of migrants and refugees through the electoral programmes of the parties in discontinuity with the legal architecture based on fundamental EU values and principles, but in line with those of the conservative majority that is emerging in many member States. During the election campaign, moreover, the Pact on Migration and Asylum, which tightened the rules for reception on European soil, was approved after years of harsh confrontation. The public discourse reflects this orientation by questioning concepts such as equality and human rights. A reading of the electoral texts drafted by parties in two Member States such as Spain and Italy, with different majorities in government, shows that this is a redefinition process as controversial as it is profound. An epistemological reflection is required to help highlight the political function of the hate speech and the social function of the ‘enemy’.